SOCIO-ECONOMIC LIFE OF SALTED FISH PROCESSING COMMUNITIES IN PANTAI INDAH, KOTO JAYA VILLAGE, MUKOMUKO CITY DISTRICT (2009-2019): KEHIDUPAN SOSIAL EKONOMI MASYARAKAT PENGOLAH IKAN ASIN DI PANTAI INDAH KELURAHAN KOTO JAYA KECAMATAN KOTA MUKOMUKO (2009-2019) - Dinda Nestiya; Meri Erawati; Kaksim (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The researcher's problem is: what motivates the community to become a salted fish manager . How is the socio-economic life of the people of Pantai Indah Koto Jaya Village 2009-2019. The objectives of this research to be achieved are. To explain what encourages the community to become salted fish managers . To explain how the socio-economic life of the people of Pantai Indah Koto Jaya Village 2009-2019. This research uses historical methods consisting of, heuristic, source criticism, interpretation, and historiography. The collection of relevant sources is carried out through literature studies and field studies. The field study was carried out using the oral history method, namely interviews with several salted fish processors, community leaders, fishermen and several people related to salted fish processing in Pantai Indah, Koto Jaya Village. Furthermore, in addition to criticizing sources, and interpreting, as well as writing / historiography. The results of the study show that, (1) Since 2009 the community has not only worked as fishermen but also as salted fish processors, this salted fish processing aims to increase the economic income of families and the community of Pantai Indah, Koto Jaya Village, (2) Since the existence of salted fish processing, the economy of families and the community of Pantai Indah, Koto Jaya Village has begun to stabilize so that it can meet the family's clothing and food needs and can even send children to school They go to college.